Enantioselective Rhodium-Catalyzed [2+2+2] Cycloaddition of Pentenyl Isocyanate and 4-Ethynylanisole: Preparation and Use of Taddolpyrrolidine Phosphoramidite - Oberg, Kevin M. (2014)
Caution, alkyl acyl azides can rapidly decompose with heat to release large amounts of nitrogen. Care should be taken during handling: do not attempt to convert neat and avoid handling neat.